"… It's Really Ultimately Very Cruel …": contrasting English intensifier collocations across EFL writing and academic spoken discourse - Recski, Leonardo Juliano (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
This paper investigates and contrasts recurrent intensifier collocations across a corpus of EFL writing – The International Corpus of Learner English – ICLE (Granger, 1993) and The Michigan Corpus of Academic Spoken English – MICASE (Simpson et al., 2002). It seeks to show that such recurrent collocations are an important part of writers and speakers' linguistic repertoire and that they may provide a window onto their lexicon. On general grounds, the results indicate that there is a great predominance of boosters over maximizers and that a limited number of maximizers and boosters are used in recurrent combinations. The analysis further revealed that maximizers tend to intensify non-gradable words while boosters tend to intensify gradable ones and that EFL writers' overuse of intensifiers appears to be associated with colloquial style and an exaggerated tone that is often considered to be inappropriate in formal academic texts.